THE IMPORTANCE OF APPLYING GOOD PRACTICES TO PREVENT POULTRY INDUSTRY POLLUTION. CASE STUDY – POULTRY FARM VASLUI COUNTY (Analele Universității București.Geografie, 2024)
The study presents the positive aspects of reducing the environmental impact on water, caused by the poultry industry, through compliant practices applied to the monitoring methodology included in the ISO 14001 implementation process for intensive poultry farming facilities at AVICOM SA in Vaslui County. The aim of the research is the comparative analysis of the results published on the analysis reports, prepared by the commercial company versus the results of the analyses carried out in the Environmental Quality Laboratory of the Faculty of Ecology and Environmental Protection of the Ecological University of Bucharest. At the same time,  possible changes in the environmental factor – water, by pollutants generated from poultry farming activities were also examined. This paper deals with the issue of maintaining water quality under the conditions of wastewater generation in poultry farms with a capacity of more than 40,000 heads per series. The study concludes with additional recommendations for the implementation of BAT standards to reduce water quality indicator values to within legal limits and to improve the quality of life for the local population.